School Climate and Bullying Prevention in Inclusive Education: Implications for Inclusive Madrasahs - Sita Husnul Khotimah; Apit Dulyapit; Husnul Khotimah; Abdul Rosyid Teguhdin Hamid; Khasanah (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2026)
Abstract School climate is often linked to bullying outcomes, but its relevance to inclusive madrasahs has not been brought together in a focused review. Following PRISMA 2020, we searched Scopus and Google Scholar on 29 March 2025 and used Publish or Perish to retrieve and manage records. Search terms combined “school climate,” “bullying,” “bullying prevention,” “inclusive education,” and “inclusive school.” The search produced 300 records; after removing 42 duplicates, we screened 258 records, assessed 60 full-text articles, and retained 29 studies for thematic synthesis. We appraised each study for clarity of purpose, methodological fit, description of context, adequacy of reporting, and relevance to the review question. Four dimensions appeared repeatedly: teacher–student relationships, peer relationships, perceived school safety, and anti-bullying policies. Supportive relationships, a stronger sense of safety, and policies that were applied consistently tended to accompany lower bullying involvement and better social inclusion. Because most studies were correlational and were conducted in general or inclusive schools rather than madrasahs, the findings do not establish effectiveness in inclusive madrasahs. They instead provide a framework that requires local testing. Rahmah, ukhuwah, and adab offer an ethical vocabulary for connecting the four dimensions with teacher practice, peer support, accessible reporting, and school governance. The evidence favors a whole-school approach over isolated anti-bullying activities. Abstrak Iklim sekolah sering dikaitkan dengan hasil perundungan, tetapi relevansinya dalam konteks madrasah inklusif belum banyak dihimpun dalam kajian yang terfokus. Dengan mengikuti pedoman PRISMA 2020, penelitian ini menelusuri artikel melalui Scopus dan Google Scholar pada 29 Maret 2025 serta menggunakan Publish or Perish untuk mengambil dan mengelola data publikasi. Kata kunci pencarian menggabungkan istilah school climate, bullying, bullying prevention, inclusive education, dan inclusive school. Hasil pencarian memperoleh 300 artikel; setelah 42 duplikasi dihapus, sebanyak 258 artikel disaring, 60 artikel teks lengkap dinilai kelayakannya, dan 29 studi dipertahankan untuk sintesis tematik. Setiap studi dinilai berdasarkan kejelasan tujuan, kesesuaian metodologi, deskripsi konteks, kecukupan pelaporan, dan relevansi terhadap pertanyaan kajian. Empat dimensi yang muncul secara berulang adalah hubungan guru–siswa, hubungan antarteman sebaya, persepsi terhadap keamanan sekolah, dan kebijakan anti-perundungan. Hubungan yang suportif, rasa aman yang lebih kuat, serta kebijakan yang diterapkan secara konsisten cenderung berkaitan dengan rendahnya keterlibatan dalam perundungan dan meningkatnya inklusi sosial. Karena sebagian besar studi bersifat korelasional dan dilakukan pada sekolah umum atau sekolah inklusif, bukan secara khusus pada madrasah, temuan ini belum dapat membuktikan efektivitasnya dalam konteks madrasah inklusif. Temuan tersebut lebih tepat dipahami sebagai kerangka awal yang masih memerlukan pengujian lokal. Nilai rahmah, ukhuwah, dan adab menawarkan kosakata etis untuk menghubungkan keempat dimensi tersebut dengan praktik guru, dukungan teman sebaya, pelaporan yang mudah diakses, dan tata kelola sekolah. Bukti yang tersedia lebih mendukung pendekatan menyeluruh berbasis sekolah dibandingkan kegiatan anti-perundungan yang bersifat terpisah atau parsial.